Development of flexible shifts in control modes and its relationship with academic achievement - Verma, Tripti; Kar, Bhoomika R. (Frontiers in Developmental Psychology, 2024)
Children transition from engaging control reactively as per the demands of a given situation, to using a proactive mode of control as an automatic response in all situations. Yet, it is crucial to study the age at which this transition takes place and to understand the development of the ability of flexible shifts in modes of control. To investigate developmental changes in this ability of children and its relationship with school readiness and academic achievement, children in the continuous age groups of 5, 6-8, and 9-11 years performed a cued switching task. The task conditions were manipulated such that in the case of "Proactive Impossible" condition, only reactive control was available; in the case of "Proactive Encouraged" condition, only proactive control was available; and in the case of "Proactive Possible" condition, both proactive and reactive control could be used. A clear preference for reactive control was evident in 5-year-old children, along with the ability to engage in proactive control when encouraged. 9-11-year-old children favored proactive control as their default mode. However, 6-8-year-olds displayed flexibility in shifting between control modes, compared to the other two age groups. This ability correlated with school readiness and academic achievement. These findings emphasize that 6-8 years of age marks the developmental period for flexible cognitive control, with the benefits of having access to and utilizing both control modes and their relationship with academic achievement.